A double-blind, placebo-controlled trial of topiramate for pathological gambling. (March 2013) - Berlin, Heather A.; Braun, Ashley; Simeon, Daphne; Koran, Lorrin M.; Potenza, Marc N.; McElroy, Susan L.; Fong, Timothy; Pallanti, Stefano; Hollander, Eric
Abstract Objectives. Pathological gambling (PG) is an impulse control disorder characterized by recurrent gambling thoughts and behaviours that impair social functioning. Earlier studies suggested that topiramate may be effective in treating some impulse control disorders. We conducted the first randomized, controlled trial of topiramate in PG. Methods. PG patients were randomized to topiramate (N = 20) or placebo (N = 22) in this 14-week, double-blind, placebo-controlled, parallel-group trial. The primary outcome measure was change in the obsessions subscale of the Yale-Brown Obsessive-Compulsive Scale Modified for Pathological Gambling. Results. Mixed regression models (time [weeks] × treatment) revealed no significant treatment effect of topiramate on the primary or secondary outcome measures. The most statistically robust findings involved reducing the Barratt Impulsiveness Scale (BIS) total score and Motor and Non-Planning subscale scores, for which topiramate outperformed placebo at merely a trend level (P < 0.1). Conclusions. The observed trend in BIS score reductions may warrant further investigation to study whether topiramate reduces clinically important impulsivity in PG. Treatment studies with larger samples and less stringent exclusion criteria are needed to produce results that can be generalized to pathological gamblers in the community.